Bartonellosis in maxillofacial region - Bistra Blagova; Daniel Markov; Nia Sаrbianova (Wolters Kluwer Medknow Publications, 2022)
Cat-scratch disease (CSD) manifests as a painful regional lymphadenopathy that occurs after a cat scratch or bites transmitted by the bacterium Bartonella henselae. The diagnosis is made by biopsy or puncture of the affected lymph nodes, which must undergo histopathology, serology, or polymerase chain reaction. An 18-year-old woman presented with progressive, painful, right submandibular adenomegaly in the absence of systemic symptoms. She denied the previous contact with cats or any other animals. A computed tomography scan of the cervix showed nodular images corresponding to the affected lymph nodes. The patient underwent a lymph node biopsy, which suggested CSD as the primary diagnosis. The biopsy does not reveal specific diagnoses. B. henselae was confirmed serologically. This case illustrates a typical evolution of CSD in which a patient is affected by subacute lymphadenopathy, but with no epidemiological history. The only certain diagnostic mean was the positive serology of Bartonella. Good general condition, despite pronounced adenomegaly without signs of toxemia, is characteristic of CSD. The lack of more accurate laboratory tests, the difficulty in culturing the pathogen, and the need for histopathology prevent the rapid diagnosis of CSD and contribute to the nonrecognition of this disease. B. henselae testing should be considered when monitoring lymphadenopathy, especially if there is subacute evolution, as in the presented case.